Comparative analysis of the banking sector competitiveness in Serbia and Montenegro - Zoran Grubišić; Sandra Kamenković; Tijana Kaličanin (Journal of Central Banking Theory and Practice, 2021)
Central banks often use certain concentration indices in their official reports to determine the degree of intensity of competition, of which the most common are the concentration ratio and the Herfindahl-Hirschman index. It is important to emphasize that when calculating the value of these indices, the National Bank of Serbia most often uses the absolute value of assets. In addition to the mentioned indices, the values of the Gini coefficient, Entropy coefficient, Rosenblatt index and graphical representation of the Lorenz curve in the period 2015-2019 are presented in this paper, using the balance sheet position loans and receivables from customers, but not including loans and receivables from banks and other financial organizations. The results of the static and dynamic analysis of concentration indicate that, compared to Montenegro, the banking sector of Serbia is characterized by a larger number of banks, less concentration on the market, and stronger intensity of competition. Although market changes are reflected in a reduced number of banks while a change in the dispersion of market shares affected the change in the market structures of the banking sectors, instability and uncertainty of the analysed sector remained unchanged in the case of both countries.
Keywords: G21; E58; L10; 330; banking sector; market concentration; market power; competition; Bank; Wettbewerb; Marktstruktur; Unternehmenskonzentration; Vergleich; Serbien; Montenegro